Interpersonal and Social Rhythm Therapy (IPSRT) sebagai Alternatif Terapi bagi Pengidap Bipolar - Kurniawan Kurniawan; Khoirunnisa Khoirunnisa; Alvira Putri Gitsyana; Mentari Yesika Putri; Anbar Fitriani; Irma Nuralawiah; Moudy Muhaiminurrohima Putri (FORIKES, 2022)
IPSRT is a psychotherapy for bipolar disorder that focuses on the stability of the rhythm of daily activities, such as time to sleep, wake up, and eat. This regular rhythm aims to reduce symptoms that occur in bipolar patients. This study aims to review IPSRT as an alternative therapy for people with bipolar disorder. The databases used in this study are Google Scholar and Pubmed which were selected based on the PRISMA flow chart, consisting of articles using the RCT method and quasi-experimental methods published in 2011-2021, nationally and internationally, full text, and free of charge. Based on the results of a review of 7 articles, 6 articles were found that said that IPSRT was effective for reducing symptoms in bipolar patients, which was seen from the quality of life of patients, as well as decreasing depressive and manic symptoms and improving social functioning in bipolar patients. It is recommended that further studies evaluate the long-term effects and recurrence of IPSRT therapy.Keywords: bipolar disorder; effectiveness; interpersonal and social rhythm therapy; psychotherapy ABSTRAK IPSRT merupakan salah satu psikoterapi gangguan bipolar yang berfokus pada kestabilan ritme aktivitas sehari-hari, seperti waktu untuk tidur, bangun, hingga makan. Teraturnya ritme ini bertujuan untuk mengurangi gejala yang terjadi pada pasien bipolar. Studi ini bertujuan untuk meninjau IPSRT sebagai alternatif terapi bagi pengidap bipolar. Database yang digunakan dalam studi ini adalah Google Scholar dan Pubmed yang terseleksi berdasarkan diagram alir PRISMA, terdiri atas artikel dengan metode RCT dan eksperimen kuasi yang diterbitkan pada tahun 2011-2021, dalam lingkup nasional dan internasional, full text, dan tidak berbayar. Berdasarkan hasil review pada 7 artikel, didapatkan 6 artikel yang mengatakan bahwa IPSRT efektif untuk menurunkan gejala pada pasien bipolar, yang dilihat dari kualitas hidup pasien, serta menurunnya gejala depresi dan maniak dan meningkatkan fungsi sosial pada pasien bipolar. Disarankan penelitian selanjutnya mengevaluasi efek jangka panjang dan kekambuhan dari terapi IPSRT.Kata kunci: gangguan bipolar; efektifitas; interpersonal and social rhythm therapy; psikoterapi